Enhancement of Electron Movement in Cytochrome c protein with Water Hydration - Pant, Amba Datt (Himalayan Physics, 2017)
Muon spin rotation and relaxation (µSR) measurements have been carried out on oxidized form of cytochrome c protein to understand the relation of electron transfer with water hydration at room temperature. Analysis of µSR data following the Risch-Kehr theory shows that intra- and inter-chain electron movement in the protein enhanced significantly. The three-dimensional diffusion of electron in wet sample (20% relative humidity) is increased around 75% with respect to that in dry sample (5% relative humidity). The Himalayan Physics Vol. 6 & 7, April 2017 (20-23)